Strategic Decisions to Overcome Turnover Problems at PT XYZ Using Regression and AHP - Prosarani, Ariadna; Putro, Utomo Sarjono (Journal Integration of Management Studies, 2025)
PT XYZ, a construction consultancy firm in Indonesia, is facing a critical issue with high employee turnover, particularly among its field project staff. This challenge adversely affects productivity continuity and imposes high recruitment and training costs. This study aims to identify the key factors influencing turnover intention and to determine the best strategic approach to address the employee turnover problem. A quantitative method, incorporating descriptive and regression analyses, was employed to investigate the relationship between job satisfaction and turnover intention. The Analytic Hierarchy Process (AHP) prioritized strategic alternatives based on financial, non-financial, and social and security benefits. Data was collected through employee questionnaires and expert interviews. The analysis revealed that, although job satisfaction levels were generally favorable, the lowest job satisfaction score was found in the Pay dimension, indicating that compensation was the primary factor contributing to dissatisfaction. A negative correlation was found between job satisfaction and turnover intention. According to the AHP results, the most important criterion was Non-Financial Benefits (weight 0.48395), while the sub-criterion for Life Insurance had the largest weight (0.59054). With a weight of 0.49089, the Performance-Based Compensation method is the most important of the three alternative strategies: Comprehensive Total Reward, Fixed Pay-Oriented, and Performance-Based Compensation. Some implementation suggestions include setting KPIs and OKRs, offering performance-based rewards, recognizing job achievements, providing limited flexibility, facilitating career development, and offering retention benefits such as life insurance. It is hoped that this study will provide a strategic foundation for creating a compensation plan tailored to the project organization's needs and the preferences of its employees.